Does doctor know best? The recent trend in medical negligence - Shuaib, Farid Sufian; Shuaib, Ibrahim Lutfi (Department of Biomedical Imaging, Faculty of Medicine, University of Malaya, 2009)
Presently, the tort system is used to regulate medical negligence litigation in Malaysia. Generally, this system provides for compensation only when a doctor or any other medical personnel assisting in the treatment of a patient is negligent. Previously, in determining whether a doctor was negligent in diagnosis, treatment and advice, the court had shown a deferential attitude towards medical judgment. This is in contrast to the attitude of the court towards other professions such as engineers and architectures where the court does not hesitate in questioning the appropriateness and reasoning of the standard practice adopted by those professionals. However, this deferential attitude which is encapsulated in the phrase “a doctor knows best” is slowly dissipating. This article will look at this development of the law by highlighting selected landmark cases that enumerate this change in court’s attitude. It is important for radiologists, in Malaysia in particular, to understand the implication in everyday practice.